Polymer and preparation method thereof, hydrogel and wound dressing

The problem of macrophage dysfunction in chronic wounds is solved by using hydrogels formed by block copolymers and glycosaminoglycanaldehyde synthesis derivatives, and effective healing of wounds is achieved.

CN119661859AActive Publication Date: 2025-03-21CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510186514.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

Due to macrophage dysfunction and phenotypic dysfunction in chronic wound patients, they are unable to effectively remove the inflammatory response of wounds, resulting in healing and prolongation.

Method used

The polymer formed by block copolymer and glycosamino polyurethane radical derivative is used to form a hydrogel through Schiff base reaction, which reduces the wound reactive oxygen species (ROS) level and regulates the burial function and phenotypic conversion of macrophages.

Benefits of technology

Effectively reduce the level of wound ROS, promote the transformation of macrophages into the M2 phenotype, reduce the inflammatory response, and promote chronic wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661859A_ABST
    Figure CN119661859A_ABST
Patent Text Reader

Abstract

The invention provides a polymer and a preparation method thereof, hydrogel and a wound dressing. The polymer is formed by a Schiff base reaction of a block copolymer and a glycosaminoglycan aldehyde derivative. Wherein the block copolymer comprises a terminal aminated polyethylene glycol segment and a polyamino acid chain segment, and the polyamino acid chain segment comprises a poly (L-methionine) segment and a poly (L-ornithine) segment. The hydrogel formed by the polymer has an immunoregulation effect, and can reduce the high active oxygen level of a wound microenvironment. Meanwhile, the two components of the block copolymer and the glycosaminoglycan aldehyde derivative in the hydrogel can enhance the phagocytic function of macrophages and promote the macrophages to convert to M2 phenotype, so that the wound microenvironment is adjusted, and the purpose of promoting chronic wound healing is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical dressings, and in particular relates to a polymer and a preparation method thereof, a hydrogel and a wound dressing. Background Art

[0002] Chronic wounds refer to wounds that have not completely healed or have no tendency to heal after standardized and complete treatment for 4 weeks or more. They mainly occur in patients with diabetes, long-term bed rest, trauma, etc. According to incomplete statistics, about 100 million patients in my country need wound treatment each year, and about 30% of them are chronic wound patients. Chronic wounds are mainly characterized by local persistent inflammatory responses. Macrophages are the main effector cells of inflammatory responses, and their function and state determine the duration of inflammation. Among them, the role of macrophage burial function and phenotypic conversion disorders in the persistent state of chronic wounds has received increasing attention. Studies have shown that the phagocytic function of macrophages can remove cell debris that may cause inflammation and immune responses, providing a clean repair environment for wounds. Macrophages secrete different cytokines through phenotypic conversion to achieve multiple key steps in wound healing. Usually, proinflammatory cytokines such as TNF-α and IL-1 secreted by macrophages in the inflammatory phase can induce inflammatory responses in the early stages of wounds, attract immune cells to the wound site, remove pathogens and necrotic tissue, and create conditions for wound healing. Macrophages in the proliferative phase secrete some anti-inflammatory cytokines, such as interleukin-10 (IL-10) and transforming growth factor-β1 (TGF-β1), which can inhibit inflammatory responses, alleviate inflammatory symptoms, and promote wound healing. However, it has been reported that the long-term inflammatory environment of chronic wounds leads to macrophage dysfunction and phenotypic disorders, making it impossible for macrophages to perform their original functions to complete wound treatment.

[0003] It is well known that reactive oxygen species (ROS) are key regulatory factors in macrophage-mediated inflammatory responses and cell proliferation during wound healing. In particular, high levels of ROS can inhibit the phagocytic ability of macrophages and weaken their ability to transform the pro-inflammatory M1 phenotype into the anti-inflammatory M2 phenotype, rendering macrophages unable to perform their original functions to complete wound healing.

[0004] Currently, in the treatment of chronic wounds, although cytokine therapy, drugs and stem cell regulation of macrophages have certain therapeutic effects, they are generally unable to appropriately regulate the efferocytosis function and phenotypic transformation of macrophages due to the influence of dosage, source and individual differences.

[0005] Therefore, providing a material that can reduce the high ROS level at the wound surface and regulate the macrophage efferocytosis function and phenotypic transformation is particularly important for clearing the inflammatory response of the wound surface and completing the repair of chronic wounds. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a polymer and a preparation method thereof, a hydrogel and a wound dressing. The hydrogel can reduce the level of reactive oxygen species (ROS) in the wound and provide a suitable microenvironment for wound repair.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a polymer formed by reacting a block copolymer and a glycosaminoglycan aldehyde derivative;

[0009] The block copolymer comprises a terminal amino-containing polyethylene glycol segment and a polyamino acid segment, wherein the polyamino acid segment comprises a poly-L-methionine segment and a poly-L-ornithine segment.

[0010] Preferably, the glycosaminoglycan aldehyde derivative is selected from one or more aldehyde derivatives of heparin, heparin derivatives, sulfated dextran, sulfated dextran derivatives, sulfated hyaluronic acid, sulfated hyaluronic acid derivatives, hyaluronic acid, hyaluronic acid derivatives, chondroitin sulfate or chondroitin sulfate derivatives.

[0011] Preferably, the oxidation degree of the glycosaminoglycan aldylation derivative is 5% to 90%.

[0012] Preferably, the molar ratio of the amino group in the block copolymer to the aldehyde group in the glycosaminoglycan aldehydic derivative is 2:1 to 1:2.

[0013] Preferably, the molar number of the poly-L-methionine segment is 50% to 99% of the polyamino acid segment.

[0014] In a second aspect, the present invention provides a method for preparing the above polymer, comprising the following steps:

[0015] S1: reacting amino-terminated polyethylene glycol with L-methionine-N-carboxyl intracyclic anhydride to obtain an intermediate;

[0016] S2: reacting the intermediate with amino-protected L-ornithine-N-carboxyl ring anhydride, followed by deprotection to obtain a block copolymer;

[0017] S3: reacting the block copolymer with a glycosaminoglycan aldylation derivative to obtain a polymer.

[0018] Preferably, the molar ratio of the amino-terminated polyethylene glycol to L-methionine-N-carboxyl intracyclic anhydride is 1:1 to 1:600.

[0019] Preferably, the molar ratio of the intermediate to the amino-protected L-ornithine-N-carboxyl intracyclic anhydride is 1:1 to 1:600.

[0020] Preferably, the reaction temperature in step S1 is room temperature and the reaction time is 2 to 4 days.

[0021] Preferably, the reaction temperature in step S2 is room temperature and the reaction time is 2 to 4 days.

[0022] Preferably, the reaction temperature in step S3 is 2-6° C. and the reaction time is 2-4 days.

[0023] In the present invention, the room temperature refers to a temperature of "10-30°C", preferably "15-25°C".

[0024] In a third aspect, the present invention provides a hydrogel formed from the above polymer.

[0025] In a fourth aspect, the present invention provides a wound dressing comprising the above-mentioned hydrogel.

[0026] Preferably, the wound dressing further comprises auxiliary materials.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a polymer, which is formed by a Schiff base reaction between a block copolymer and a glycosaminoglycan aldehyde derivative. The introduction of the glycosaminoglycan aldehyde derivative can regulate the transformation of macrophages to the M2 phenotype. In the present invention, the block copolymer includes an amino-terminated polyethylene glycol segment and a polyamino acid segment, wherein the amino-terminated polyethylene glycol segment can improve the water solubility of the polyamino acid; the polyamino acid segment includes a poly-L-methionine segment and a poly-L-ornithine segment. The presence of the poly-L-methionine segment can eliminate excessive ROS, and the presence of the poly-L-ornithine segment can enhance the sustained burial behavior of macrophages.

[0029] The hydrogel formed by the above polymer of the present invention has an immunomodulatory effect and can reduce the high ROS level of the wound microenvironment. At the same time, the two components of the block copolymer and the glycosaminoglycan aldehyde derivative in the hydrogel can synergistically regulate the function of macrophages through different pathways, promote the transformation of macrophages to M2 phenotype, so as to regulate the wound microenvironment and achieve the purpose of promoting the healing of chronic wounds, and animal experiments have verified the effectiveness of chronic wound treatment. Therefore, the hydrogel provided by the present invention helps to reconstruct vascular function, collagen deposition and epithelialization, and solves the problem of clinical chronic wounds being difficult to heal. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is the mPEG obtained in Example 1 2k -b-(Met 25 -b-Orn5) H NMR spectrum;

[0031] Figure 2 is the H NMR spectrum of aldehyded hyaluronic acid;

[0032] Figure 3 Circular dichroism results of mPMO / OHA hydrogel, mPML / OHA hydrogel, and mPMO / ODEX hydrogel;

[0033] Figure 4 Live / dead staining results of mPMO / OHA hydrogel, mPML / OHA hydrogel, and mPMO / ODEX hydrogel;

[0034] Figure 5 The CCK-8 results of mPMO / OHA hydrogel, mPML / OHA hydrogel, and mPMO / ODEX hydrogel are shown;

[0035] Figure 6 The CCK-8 results of mPMO / OHA hydrogel, mPML / OHA hydrogel, and mPMO / ODEX hydrogel under 0.2 mM H2O2 conditions are shown;

[0036] Figure 7 The flow cytometry analysis of macrophage phenotype after co-culture of mPMO / OHA hydrogel, mPML / OHA hydrogel, and mPMO / ODEX hydrogel with RAW264.7 cells;

[0037] Figure 8 This is a diagram of the macrophage efferocytosis ability after co-culture of mPMO / OHA hydrogel, mPML / OHA hydrogel, and mPMO / ODEX hydrogel with RAW264.7 cells. DETAILED DESCRIPTION

[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The invention provides a polymer, which is formed by reacting a block copolymer and a glycosaminoglycan aldehyde derivative.

[0040] In the present invention, the amino group in the block copolymer and the aldehyde group in the glycosaminoglycan aldehyde derivative undergo Schiff base reaction, thereby connecting the block copolymer and the glycosaminoglycan aldehyde derivative together. Therefore, the aldehyde content in the glycosaminoglycan aldehyde derivative is more critical, and the aldehyde content is positively correlated with the degree of oxidation. In the present invention, the degree of oxidation in the glycosaminoglycan aldehyde derivative is 5% to 90%, preferably about 20%. If the aldehyde content is too low, the modulus of the hydrogel prepared subsequently will be too low, otherwise, it will affect the biological function of glycosaminoglycans.

[0041] In some embodiments of the present invention, the molar ratio of the amino group in the block copolymer to the aldehyde group in the glycosaminoglycan aldehydic derivative is 2:1 to 1:2, specifically 2:1, 1:1, 1:2, etc.

[0042] In the present invention, the block copolymer comprises an amino-terminated polyethylene glycol segment and a polyamino acid segment, wherein the molecular weight of the polyethylene glycol in the amino-terminated polyethylene glycol segment is between 200 and 40,000 kDa, preferably 2,000 kDa.

[0043] The polyamino acid segment includes a poly-L-methionine segment and a poly-L-ornithine segment, and the molar number of the poly-L-methionine segment accounts for 50% to 99% of the polyamino acid segment, preferably 5 / 6. The present invention limits the ratio of the above-mentioned L-methionine because a too high ratio of methionine will result in a too low gelling temperature of the hydrogel, which is not conducive to storage. A too low ratio of methionine will result in a too high gelling temperature, which is not conducive to practical application.

[0044] The present invention adopts an amino-terminated polyethylene glycol segment, which can attack the carbonyl carbon atom with the help of the amino group, thereby initiating a ring-opening reaction and realizing the combination of polyethylene glycol and L-methionine. Subsequently, L-ornithine and L-methionine are connected through the ring-opening reaction to obtain a block copolymer.

[0045] In the present invention, the glycosaminoglycan aldehyde derivative is selected from one or more aldehyde derivatives of heparin, heparin derivatives, sulfated dextran, sulfated dextran derivatives, sulfated hyaluronic acid, sulfated hyaluronic acid derivatives, hyaluronic acid, hyaluronic acid derivatives, chondroitin sulfate or chondroitin sulfate derivatives, preferably an aldehyde derivative of hyaluronic acid, that is, aldehyde hyaluronic acid. In some embodiments of the present invention, when the glycosaminoglycan aldehyde derivative is selected from aldehyde hyaluronic acid, the polymer can be represented by a polymer as shown in Formula I:

[0046] Formula I;

[0047] Where x = any integer between 5 and 900, y = any integer between 1 and 600, z = any integer between 1 and 600;

[0048] “ ” indicates the linking site, which is used to connect glycosaminoglycan or polyamino acid segments, and “b” represents block copolymerization.

[0049] The present invention also provides a method for preparing the above polymer, comprising the following steps:

[0050] S1: reacting amino-terminated polyethylene glycol with L-methionine-N-carboxyl intracyclic anhydride to obtain an intermediate;

[0051] S2: reacting the intermediate with amino-protected L-ornithine-N-carboxyl ring anhydride, followed by deprotection to obtain a block copolymer;

[0052] S3: reacting the block copolymer with a glycosaminoglycan aldylation derivative to obtain a polymer.

[0053] According to the present invention, firstly, the terminal amino polyethylene glycol is reacted with L-methionine-N-carboxyl ring anhydride to obtain an intermediate. In the present invention, the terminal amino polyethylene glycol is generally synthesized first. The molecular weight of the polyethylene glycol is generally between 200 and 40000 kDa, preferably 2000 kDa. The present invention has no particular restrictions on the method for synthesizing terminal amino polyethylene glycol, and it can be carried out according to means well known to those skilled in the art. The L-methionine-N-carboxyl ring anhydride can be prepared according to methods well known to those skilled in the art, or directly purchased commercially. In some embodiments of the present invention, the molar ratio of the terminal amino polyethylene glycol to the L-methionine-N-carboxyl ring anhydride is 1:1~1:600, preferably 1:10~1:50. The temperature of the reaction is room temperature, and the time is 2~4 days, preferably 3 days.

[0054] Then, according to the present invention, the intermediate is reacted with amino-protected L-ornithine-N-carboxyl cyclic anhydride, preferably benzyloxycarbonyl-L-ornithine-N-carboxyl cyclic anhydride, and then deprotected to obtain a block copolymer. The amino-protected L-ornithine-N-carboxyl cyclic anhydride can be prepared according to methods well known to those skilled in the art, or a commercially available product can be directly purchased.

[0055] In some embodiments of the present invention, the intermediate is preferably reacted at a molar ratio of 1:1 to 1:600, preferably 1:5 to 1:200, to obtain a block copolymer. The reaction is preferably carried out at room temperature for 2 to 4 days, preferably 3 days.

[0056] In some preferred embodiments of the present invention, the terminal amino polyethylene glycol is generally dehydrated and then reacted with L-methionine-N-carboxyl ring anhydride. The dehydration method is a method well known to those skilled in the art and is not particularly limited. The present invention preferably removes water by azeotropically dehydrating the terminal amino polyethylene glycol and toluene, and then removing the toluene; the temperature of the azeotropic dehydration is preferably 110-125°C; the time of the azeotropic dehydration is preferably 2-3 h; the method of removing toluene is preferably vacuum extraction; the reaction is preferably carried out in an organic solvent; the organic solvent is an organic solvent well known to those skilled in the art and is not particularly limited. The present invention is preferably dry anhydrous N,N-dimethylformamide (DMF); the reaction temperature is room temperature, preferably 10-40°C, more preferably 15-25°C; the reaction time is preferably 2-4 days, more preferably 3 days.

[0057] Then, add amino-protected L-ornithine-N-carboxyl ring anhydride to react, and preferably replace nitrogen 2 to 3 times before the reaction. The reaction temperature is room temperature, preferably 10 to 40°C, more preferably 15 to 25°C; the reaction time is preferably 2 to 4 days, more preferably 3 days. After the reaction is completed, preferably precipitate with ice ether, filter with a Buchner funnel, and vacuum dry to obtain a light yellow polymer, which is weighed.

[0058] Then, the obtained product is deprotected, and the deprotection means can be carried out according to means familiar to those skilled in the art. After deprotection, the present invention preferably dissolves the product with trifluoroacetic acid (TFA) and reacts with hydrobromic acid / acetic acid solution for 1 h, and then precipitates with ice ether again, filters with a Buchner funnel, and the solid is dissolved in an appropriate amount of DMF and loaded into a dialysis bag, dialyzed in deionized water and freeze-dried to obtain a block copolymer shown in formula C. The dialysis bag is preferably a 3500 Da dialysis bag; the dialysis time is preferably 2 to 4 days, more preferably 3 days.

[0059] In the present invention, the glycosaminoglycan aldehyde derivative is preferably prepared according to the following method: glycosaminoglycan is fully dissolved in water, preferably double distilled water (Milli-Q), sodium periodate is slowly added dropwise to the glycosaminoglycan solution in the dark, reacted at room temperature for 1 to 5 hours, preferably 2 to 4 hours, ethylene glycol is added to react with the remaining sodium periodate, stirring is continued for 1 to 5 hours to terminate the reaction, placed in a dialysis bag, dialyzed in deionized water and freeze-dried to obtain a glycosaminoglycan aldehyde derivative. The dialysis bag is preferably a 3500 Da dialysis bag; the dialysis time is preferably 1 to 4 days, more preferably 2 days.

[0060] As described in the above related content, in the present invention, the aldehydation content in the aldehydation derivatives of glycosaminoglycans is more critical. Therefore, the present invention determines the aldehydation content in the aldehydation derivatives of glycosaminoglycans by the hydroxylamine hydrochloride method to ensure that the aldehydation content is within the target range.

[0061] According to the present invention, after obtaining the block copolymer and the glycosaminoglycan aldehyde derivative, the block copolymer and the glycosaminoglycan aldehyde derivative are preferably reacted to obtain a polymer. Wherein, the block copolymer and the glycosaminoglycan aldehyde derivative are preferably reacted in a ratio of 1:(1-2) in which the molar ratio of the amino group in the block copolymer to the aldehyde group in the glycosaminoglycan aldehyde derivative is 1:(1-2), and the reaction is preferably carried out under solvent conditions, the reaction temperature is 2-6°C, preferably 4°C, and the reaction time is 2-4 days, preferably 3 days.

[0062] In some embodiments of the present invention, when the glycosaminoglycan aldehyde derivative is aldehyde-modified hyaluronic acid, the preparation method of the polymer is as follows:

[0063] S1: reacting the compound represented by formula A with L-methionine-N-carboxyl intracyclic anhydride to obtain a compound represented by formula B;

[0064] S2: reacting the compound represented by formula B with L-ornithine-N-carboxyl intracyclic anhydride whose amino group is protected, followed by deprotection to obtain a block copolymer represented by formula C;

[0065] S3: reacting the block copolymer represented by formula C with aldehyde-modified hyaluronic acid to obtain a polymer represented by formula I;

[0066] Formula A; Formula B; Formula C;

[0067] Wherein, b represents block copolymerization.

[0068] The specific parameters in the above method are as described in the above related content and will not be repeated here.

[0069] In some embodiments of the present invention, in the block copolymer of formula C, x can be any integer between 5 and 900, y can be any integer between 1 and 600, and z can be any integer between 1 and 100.

[0070] Specifically, in some embodiments of the present invention, in the prepared block copolymer represented by formula C, x=45, y=25, z=5;

[0071] Or x=45, y=40, z=1;

[0072] Or x=45, y=15, z=25;

[0073] Or x=180, y=100, z=25;

[0074] Or x=180, y=160, z=4;

[0075] Or x=180, y=60, z=100.

[0076] The present invention also provides a hydrogel formed from the above polymer (e.g., the polymer represented by formula I).

[0077] In some embodiments of the present invention, the hydrogel is prepared according to the following method:

[0078] A polymer solution is prepared in a phosphate buffered saline solution, and a corresponding mass of glycosaminoglycan aldehyde derivative is added according to the molar ratio of aldehyde group to amino group, and stirred at 2-6°C for 2-4 days.

[0079] It should be noted that the concentration of the polymer solution can be adjusted according to the actual situation. If the polymer needs to gel under low temperature conditions, it is preferred to use a polymer with a high degree of methionine polymerization to prepare a high-concentration polymer solution. If the polymer needs to gel under high temperature conditions, it is preferred to use a polymer with a low degree of methionine polymerization to prepare a low-concentration polymer solution.

[0080] The present invention also provides a wound dressing, comprising the above hydrogel and optional auxiliary materials, wherein the auxiliary materials can be antibacterial agents, moisturizers, hemostatic agents, breathable materials, adhesives, drug carriers or components that promote cell growth (such as bioactive components such as fibroblast growth factor (FGF) and collagen).

[0081] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0082] Example 1 Poly(ethylene glycol)-block-poly(L-methionine-block-L-ornithine) (methoxypoly(ethylene glycol)-block-poly(L-methionine-block-L-Ornithine), abbreviated as mPEG 2k -bP(Met 25 Synthesis of -b-Orn5)

[0083] This embodiment provides a mPEG 2k -bP(Met 25 -b-Orn5), the synthesis route of which is as follows:

[0084] ;

[0085] Among them, x=45, y=25, z=5;

[0086] The specific steps are:

[0087] (1) Synthesis of amino-terminated mPEG 2k :40 g mPEG 2k Dissolve it fully with 200 mL of dichloromethane, add 9.6 g of p-Toluenesulfonyl Chloride (PTSC) and 2.8 g of potassium hydroxide in sequence, stir for 7 days, pour into a separatory funnel, wash with ice saturated sodium chloride solution 6 times, make the lower organic phase product as clear as possible, and dry the lower product with anhydrous magnesium sulfate (MgSO4) at room temperature overnight after separation. The next day, filter out the magnesium sulfate with a sand core funnel, concentrate it by rotary evaporation, and then precipitate the liquid with ice ether. After stirring for 15 min, filter it with a Buchner funnel, and vacuum dry it at room temperature for 12 h to obtain the polymer. The polymer obtained by the reaction is fully dissolved with 10 times the mass volume of ammonia water of the polymer, add the same mass of ammonium chloride, react at room temperature for 7 days, extract the organic phase with dichloromethane, wash the organic phase with ice saturated sodium chloride solution twice, and dry it with anhydrous MgSO4 at room temperature overnight. The next day, magnesium sulfate was filtered out with a sand core funnel, and then precipitated with ice ether again, dried with a Buchner funnel, and dried under vacuum at room temperature to obtain the final product mPEG. 2k -NH2 (where mPEG 2k refers to the molecular weight of mPEG being 2000 kDa);

[0088] (2) Synthesis of two amino acids NCA: Prepare a dry three-necked round-bottom flask, pass nitrogen, add 300 mL of tetrahydrofuran (THF), weigh 15 g of L-methionine (L-Met) / L-ornithine (L-Orn(z)-OH) and 20 g of triphosgene (Bis(trichloromethyl)carbonate, BTC) and add them to the flask. Place in an oil bath at 48°C. After 1 hour, the liquid becomes transparent. Increase the nitrogen flow rate to blow away THF as much as possible. When 20-30 mL of THF is left, use ice n-hexane to precipitate. Stir rapidly during precipitation. Use a Buchner funnel to filter to obtain a solid product. Then use an appropriate amount of ice ethyl acetate to dissolve the solid, wash it three times with anhydrous saturated sodium chloride solution, add it to a conical flask, add an appropriate amount of anhydrous magnesium sulfate and dry it overnight at -20°C. The next day, the filtrate was filtered with a G4 sand core funnel, and the filtrate was connected to a cold trap and the solvent was removed with a vacuum pump, and then recrystallized and purified (methionine does not need to be recrystallized) to obtain L-methionine-N-carboxyl ring anhydride (L-Met NCA) and benzyloxycarbonyl-L-ornithine-N-carboxyl ring anhydride (ZL-Orn NCA).

[0089] (3) Synthesis of mPEG2k-bP (Met25-b-Orn5): Add 1 g mPEG-NH2 to 200 mL dry toluene, remove water by azeotropic reaction at 125°C for 2 h, drain the toluene with a vacuum pump, add 40 mL dry anhydrous N,N-dimethylformamide (DMF) and 2.17 g L-Met NCA in turn, react at room temperature for 3 days, replace nitrogen three times, add 0.73 g ZL-Orn NCA, and continue to react at room temperature for 3 days. Use ice ether to precipitate, filter with a Buchner funnel, and vacuum dry to obtain a light yellow polymer, which is weighed. After that, the protecting group was deprotected, the product was dissolved with 10 times the mass volume of trifluoroacetic acid (TFA), and then three times the mass volume of hydrobromic acid / acetic acid solution was added to react for 1 h, and then precipitated with ice ether again, filtered with a Buchner funnel, and the solid was dissolved in an appropriate amount of DMF and loaded into a 3500 Da dialysis bag, dialyzed in deionized water for 3 days, and then freeze-dried to obtain mPEG 2k -b-(Met 25 -b-Orn5) (abbreviated as: mPMO).

[0090] Nuclear magnetic resonance imaging of mPEG 2k -b-(Met 25 -b-Orn5) was analyzed and its nuclear magnetic resonance hydrogen spectrum was obtained as follows Figure 1 As shown, the successful synthesis of mPMO was demonstrated.

[0091] Example 2 Synthesis of OHA

[0092] Dissolve 1 g of hyaluronic acid in 100 mL of double distilled water (Milli-Q), dissolve 1.01 g, 1.35 g, 1.52 g, 1.69 g, 1.92 g, 2.14 g and 2.37 g of sodium periodate in 30 mL of double distilled water (Milli-Q), respectively, slowly add sodium periodate dropwise to the hyaluronic acid solution in the dark, react at room temperature for 2 h, add 2 ml of ethylene glycol, continue stirring for 1 h to terminate the reaction, put into a 3500 Da dialysis bag, dialyze in deionized water for 2 days, and then freeze-dry to obtain hyaluronic acid with seven oxidation degrees.

[0093] The aldehyded hyaluronic acid was analyzed by nuclear magnetic resonance, and its nuclear magnetic resonance hydrogen spectrum was obtained as follows: Figure 2 As shown, 1735 cm -1 The stretching vibration of the aldehyde group appeared at the position, proving the successful synthesis of OHA.

[0094] The oxidation degree and aldehyde content of OHA are determined by the hydroxylamine hydrochloride method. The aldehyde group in OHA reacts with hydroxylamine hydrochloride to generate the compound oxime while releasing a molecule of hydrochloric acid. The oxidation degree and aldehyde content of OHA can be indirectly measured by measuring the pH value through acid-base titration.

[0095] Among them, the oxidation degree of oxidized hyaluronic acid (%):

[0096] ;

[0097] V: volume of NaOH consumed by hyaluronic acid after oxidation (mL), V0: volume of NaOH consumed by unoxidized hyaluronic acid (mL);

[0098] M: molar concentration of NaOH (mol / L), W: mass of oxidized hyaluronic acid (g);

[0099] M W : Molar mass of the structural unit of hyaluronic acid (g / mol).

[0100] After testing, the degrees of oxidation of the oxidized hyaluronic acid obtained by adding 1.01 g, 1.35 g, 1.52 g, 1.69 g, 1.92 g, 2.14 g and 2.37 g of sodium periodate were 19.0%, 28.4%, 45.5%, 47.4%, 64.5%, 73.3% and 80.8%, respectively, and the aldehyde contents were 38.0%, 56.8%, 91.0%, 94.8%, 129.0%, 146.6% and 161.6%, respectively.

[0101] Since polysaccharides with an oxidation degree of about 20% can provide the maximum number of aldehyde units while retaining their biological functions, OHA with an oxidation degree of 19% was used in the subsequent preparation of mPMO / OHA hydrogels, that is, the aldehyde content was 38%.

[0102] Example 3 Synthesis of mPMO / OHA hydrogel

[0103] A solution of the polymer (ie, mPMO) with a concentration of 8 wt % was prepared in phosphate buffered saline, and a corresponding amount of OHA was added at a molar ratio of aldehyde groups to amino groups of 1:1, and stirred at 4°C for 3 days.

[0104] Comparative Example 1 Synthesis of mPML / OHA hydrogel

[0105] (1) Synthesis of lysine NCA: Prepare a dry three-necked round-bottom flask, pass nitrogen, add 300 mL of tetrahydrofuran (THF), weigh 15 g of L-lysine (L-Lys(z)-OH) and 20 g of triphosgene (Bis(trichloromethyl)carbonate, BTC) and add them to the flask. Place in an oil bath at 48°C. After 1 hour, the liquid becomes transparent. Increase the nitrogen flow rate to blow away THF as much as possible. When 20-30 mL of THF is left, use glacial n-hexane to precipitate. Stir rapidly during precipitation. Use a Buchner funnel to filter to obtain a solid product. Then use an appropriate amount of glacial ethyl acetate to dissolve the solid, wash it three times with anhydrous saturated sodium chloride solution, add it to a conical flask, add an appropriate amount of anhydrous magnesium sulfate and dry it overnight at -20°C. The next day, the filtrate was filtered with a G4 sand core funnel, and the filtrate was connected to a cold trap and the solvent was removed with a vacuum pump, and then recrystallized and purified to obtain benzyloxycarbonyl-L-lysine-N-carboxyl ring anhydride (ZL-Lys NCA);

[0106] (2) Synthesis of mPEG 2k -bP(Met 25 -b-Lys5): Add 1 g mPEG-NH2 to 200 mL dry toluene, remove water by azeotropic reaction at 125°C for 2 h, drain toluene with a vacuum pump, add 40 mL dry anhydrous N,N-dimethylformamide (DMF) and 2.17 g L-Met NCA in turn, react at room temperature for 3 days, replace nitrogen three times, add 0.77 g ZL-Lys NCA, and continue to react at room temperature for 3 days. Use ice ether to precipitate, filter with a Buchner funnel, and vacuum dry to obtain a light yellow polymer, which is weighed. After that, the protecting group is deprotected, the product is dissolved with 10 times the mass volume of trifluoroacetic acid (TFA), and then three times the mass volume of hydrobromic acid / acetic acid solution is added to react for 1 h, and then precipitated with ice ether again, filtered with a Buchner funnel, and the solid is dissolved in an appropriate amount of DMF and loaded into a 3500 Da dialysis bag. After dialyzing in deionized water for 3 days, it is freeze-dried to obtain mPEG 2k -b-(Met 25 -b-Lys5) (abbreviated as: mPML).

[0107] 3) Synthesis of mPML / OHA hydrogel: A solution of mPML polymer with a concentration of 8% was prepared in phosphate buffered saline, and the corresponding mass of OHA was added at a molar ratio of aldehyde group to amino group of 1:1, and stirred at 4°C for 3 days.

[0108] Comparative Example 2 Synthesis of mPMO / ODEX hydrogel

[0109] (1) Synthesis of oxidized dextran (ODEX):

[0110] Dissolve 1 g of dextran in 100 mL of double distilled water (Milli-Q), dissolve 131 mg, 261 mg, 524 mg, and 786 mg of sodium periodate in 30 mL of double distilled water (Milli-Q), respectively, slowly add sodium periodate dropwise to the hyaluronic acid solution in the dark, react at room temperature for 2 h, add 2 ml of ethylene glycol, continue stirring for 1 h to terminate the reaction, put into a 3500 Da dialysis bag, dialyze in deionized water for 2 days, and then freeze-dry to obtain 4 dextran with different oxidation degrees.

[0111] The oxidation degree and aldehyde content of ODEX are determined by the hydroxylamine hydrochloride method. The aldehyde group in ODEX reacts with hydroxylamine hydrochloride to generate the compound oxime while releasing a molecule of hydrochloric acid. The oxidation degree and aldehyde content of OHA can be indirectly measured by measuring the pH value by acid-base titration.

[0112] Among them, the oxidation degree of oxidized dextran (%):

[0113] ;

[0114] V: volume of NaOH consumed by oxidized dextran (mL), V0: volume of NaOH consumed by unoxidized dextran (mL);

[0115] M: molar concentration of NaOH (mol / L), W: mass of oxidized dextran (g);

[0116] M W : Molar mass of the structural unit of dextran (g / mol).

[0117] After testing, the oxidation degrees of the oxidized dextran obtained by adding 131 mg, 261 mg, 524 mg and 786 mg of sodium periodate were 18.4%, 32.4%, 56.7% and 75.3%, respectively, and the aldehyde contents were 36.8%, 64.8%, 113.4% and 150.6%, respectively.

[0118] 2) Synthesis of mPMO / ODEX hydrogel: A solution of mPMO polymer with a concentration of 8% was prepared in phosphate buffered saline, and the corresponding mass of ODEX was added at a molar ratio of aldehyde group to amino group of 1:1, and stirred at 4°C for 3 days.

[0119] Circular dichroism tests were performed on the mPMO / OHA hydrogel (OHA oxidation degree of 19%), mPML / OHA hydrogel, and mPMO / ODEX (ODEX oxidation degree of 18.4%) hydrogel obtained in Example 3 and Comparative Examples 1-2 to study the secondary structure in the hydrogel. The results are as follows: Figure 3As shown, it can be seen that all three hydrogels have a positive peak at 195 nm and two negative peaks at 210 nm and 225 nm, which are the characteristic peaks of α-helix. By fitting the proportion of secondary structure, it was found that there was no significant difference in the proportion of secondary structure of the three hydrogels, indicating that the methionine segment dominated the formation of the secondary structure, and the polysaccharide and lysine segments did not have a significant effect on the secondary structure of the hydrogel. And as the temperature increased from 10°C to 70°C, the intensity of the three absorption peaks decreased, indicating that as the temperature increased, the change of the polyamino acid segment would cause the material to undergo a solution-gel phase transition, and the secondary structure remained stable.

[0120] The present invention uses HaCat cells, and after they adhere to the wall, they are co-cultured with mPML / OHA hydrogel, mPMO / OHA hydrogel, and mPMO / ODEX hydrogel materials for 24 hours, and the toxic and side effects of the materials are detected by the dye Calcein-AM / PI live / dead cell staining method and CCK-8 method. Figure 4 As shown in Figure 2, in each field of view, the number of apoptotic cells in each group is similar, and the cell activity of different hydrogel material groups is higher than that of the blank group (Control group, i.e., single HaCat cells without hydrogel), indicating that the hydrogel has no obvious toxicity to the cells. Figure 5 shown.

[0121] Hydrogen peroxide (H2O2) is an important reactive oxygen species (ROS) that plays a dual role in cell life activities. On the one hand, under normal physiological conditions, ROS (including hydrogen peroxide) are produced in cells and play an important role in signal transduction; on the other hand, when ROS are overproduced or insufficiently cleared, they will cause oxidative stress to cells, leading to cell damage and disease. The present invention uses the CCK-8 method to detect the protective ability of mPML / OHA hydrogel, mPMO / OHA hydrogel, and mPMO / ODEX hydrogel on HaCat cells exposed to 200 μM H2O2. The results are as follows: Figure 6 As shown in the figure (wherein, the Control group, i.e., single HaCat cells without adding hydrogel, and the H2O2 group, HaCat cells and hydrogel co-cultured in a medium containing 0.2 mM H2O2), it can be seen that there is no significant difference in cell viability between different hydrogel groups, but all are higher than the Control group. This is because L-methionine can play a protective role, indicating that the hydrogel provided by the present invention has an excellent antioxidant effect, ensuring that the hydrogel can be used in subsequent experiments on living organisms. The results are shown in Figure 6 shown.

[0122] Lipopolysaccharide (LPS) is a component of bacterial cell walls that can stimulate immune cells, including macrophages. In chronic wounds, LPS can activate macrophages and trigger a persistent inflammatory response, thereby affecting the wound healing process. The present invention co-cultures RAW264.7 cells with mPML / OHA hydrogel, mPMO / OHA hydrogel, and mPMO / ODEX hydrogel in an LPS and H2O2 environment for one day, and then digests them into single-cell suspensions for flow cytometry detection. The gating process is as follows: after removing adhesions, live cells are selected, and CD80 or CD206 positive cells are selected from the F4 / 80 strong positives, which are the M1 or M2 macrophage gates. The results are as follows Figure 7 As shown (wherein, Control group, i.e., single HaCat cells, without adding hydrogel, LPS and H2O2; LPS+H2O2 group, i.e., HaCat cells co-cultured with LPS and H2O2, without adding hydrogel), it can be seen that the use of mPMO / OHA hydrogel can effectively increase the proportion of M2 macrophages.

[0123] The present invention verifies the regulation of different hydrogels on macrophage efferocytosis by treating bone marrow-derived neutrophils for apoptosis and co-culturing them with RAW264.7 cells exposed to H2O2 and LPS and mPML / OHA hydrogel, mPMO / OHA hydrogel, and mPMO / ODEX hydrogel. Figure 8 As shown in the results (Control group, i.e., single HaCat cells without addition of hydrogel, LPS and H2O2, LPS+H2O2 group, i.e., HaCat cells co-cultured with LPS and H2O2 without addition of hydrogel), mPM / OHA hydrogel can significantly enhance the phagocytic ability of macrophages on apoptotic cells.

[0124] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A polymer, characterized in that The polymer is formed by reacting a block copolymer and a glycosaminoglycan aldehyde derivative; The block copolymer comprises a terminal amino-containing polyethylene glycol segment and a polyamino acid segment, wherein the polyamino acid segment comprises a poly-L-methionine segment and a poly-L-ornithine segment.

2. The polymer according to claim 1, characterized in that The glycosaminoglycan aldehyde derivative is selected from one or more aldehyde derivatives of heparin, heparin derivatives, sulfated dextran, sulfated dextran derivatives, sulfated hyaluronic acid, sulfated hyaluronic acid derivatives, hyaluronic acid, hyaluronic acid derivatives, chondroitin sulfate or chondroitin sulfate derivatives.

3. The polymer according to claim 1 or 2, characterized in that The oxidation degree of the glycosaminoglycan aldylation derivative is 5% to 90%.

4. The polymer according to claim 1, characterized in that The molar ratio of the amino group in the block copolymer to the aldehyde group in the glycosaminoglycan aldehyde derivative is 2:1 to 1:

2.

5. The polymer according to claim 1, characterized in that The molar number of the poly-L-methionine segment is 50% to 99% of the polyamino acid segment.

6. A method for preparing a polymer as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1: reacting amino-terminated polyethylene glycol with L-methionine-N-carboxyl intracyclic anhydride to obtain an intermediate; S2: reacting the intermediate with amino-protected L-ornithine-N-carboxyl ring anhydride, followed by deprotection to obtain a block copolymer; S3: reacting the block copolymer with a glycosaminoglycan aldylation derivative to obtain a polymer.

7. The preparation method according to claim 6, characterized in that: The molar ratio of the amino-terminated polyethylene glycol to the L-methionine-N-carboxyl intracyclic anhydride is 1:1 to 1:600; The molar ratio of the intermediate to the amino-protected L-ornithine-N-carboxyl ring anhydride is 1:1 to 1:600; The reaction temperature in step S1 is room temperature and the reaction time is 2 to 4 days; The reaction temperature in step S2 is room temperature and the reaction time is 2 to 4 days; The reaction temperature in step S3 is 2-6° C. and the reaction time is 2-4 days.

8. A hydrogel, characterized in that The method is formed by a polymer according to any one of claims 1 to 5 or a polymer prepared by the preparation method according to any one of claims 6 and 7.

9. A wound dressing, characterized in that: Comprising the hydrogel according to claim 8.

10. The wound dressing according to claim 9, characterized in that: The wound dressing also includes auxiliary materials.

Citation Information

Patent Citations

  • Active oxygen responsive polyamino acid bonded glycosaminoglycan hydrogel as well as preparation method and application thereof

    CN114958008A